STUDI KASUS: KECEMASAN DALAM KEHAMILAN DAPAT MENGHAMBAT PROSES PERSALINAN - Siska Febrina Fauziah (Poltekkes Kemenkes Maluku, 2021)
At the end stage of pregnancy, a certain amount of anxiety is considered a normal thing experienced by a woman in preparation for the upcoming birth. In some women, this feeling develops into fear of childbirth which might have negative consequences on both the mother and the baby. This case study describes the anxiety experienced by Mrs. G, a 27-years-old primigravida, which caused obstacles in the labor process. The anxiety arose because Mrs. G had no felt any signs of labor until a week after the due date. Counseling and personal approaches are carried out to deal with anxiety, as well as the use of hot herbal compress for relaxation. Meanwhile, uterine contraction was induced naturally by doing oxytocin massage and acupressure on the BL 67 point. Midwifery care provided in this case could reduce anxiety and stimulate uterine contractions to initiate the labor process. Comprehensive and continuous support and assistance from health workers is needed to obtain optimal midwifery care outcomes.